Pressuring of Acupoints as a Complement to the Diagnosis of Stifle Diseases in Horses - Luiza P.R. Mariani; Flávia Sampaio; Andressa B. Silveira; Luis F. Bastos; Saulo H. Weber; Pedro V. Michelotto (Medical Association of Pharmacopuncture Institute, 2019)
Diseases of the stifle joint remain a challenge for veterinarians. The objective of this study was to achieve a valuable acupuncture suggestive diagnosis to be considered for stifle joint diseases in horses. Thirty-nine nonlame horses involved in different activities were assessed. Acupuncture was independently performed by two evaluators. Reactions of the animal when pressurizing the point suggestive of stifle disease (PSSD), Bladder-20 and/or Bladder-21, were considered as the inclusion criteria for inclusion in the stifle group (SG, n = 31), and the animals with no reactions were assigned to the control group (n = 8). Radiographic and ultrasonographic examinations were performed and evaluated by two independent professionals blinded to the group allocation. Thermographic examination of the PSSD and stifles was also performed, after acclimatization. The ultrasound scores and radiographic findings were higher in the SG than in the control group. Thermography evidenced increased temperature in the PSSD and stifles in the SG. The minimum acupuncture diagnostic criteria for stifle joint disease had a sensitivity of 87.5% and a specificity of 57.0%, and the addition of the acupoints Gallbladder-dorsal tuber coxae, Gallbladder-27, and Spleen-13 to the minimum diagnostic criteria improved sensitivity and specificity. In conclusion, assessing the reaction at the demonstrated acupoints can facilitate a diagnosis of a potential stifle lesion. Keywords: acupuncture, equine, horse, radiography, ultrasonography